Epidermal and dermal characteristics in skin equivalent after systemic and topical application of skin care ingredients - Vicanova, Jana; Bouez, Charbel; Lacroix, Sophie; Lindmark, Lars; Damour, Odile (Annals of the New York Academy of Sciences, 2006)
Effects of active ingredients from topical and systemic skincare products on structure and organization of epidermis, dermal-epidermal junction (DEJ), and dermis were examined using an in vitro reconstructed skin equivalent (SE). Imedeen Time Perfection (ITP) ingredients (a mixture of BioMarine Complex, grape seed extract, tomato extract, vitamin C) were supplemented systemically into culture medium. Kinetin, an active ingredient from Imedeen Expression Line Control Serum, was applied topically. Both treatments were tested separately or combined. In epidermis, all treatments stimulated keratinocyte proliferation, showing a significant increase of Ki67-positive keratinocytes (P < 0.05). Kinetin showed a twofold increase of Ki67-positive cells, ITP resulted in a fivefold, and ITP+kinetin showed a nine-fold increase. Differentiation of keratinocytes was influenced only by kinetin since filaggrin was found only in kinetin and kinetin+ITP samples. At the DEJ, laminin 5 was slightly increased by all treatments. In dermis, only ITP increased the amount of collagen type I. Both kinetin and ITP stimulated formation of fibrillin-1 and elastin deposition. The effect of kinetin was seen in upper dermis. It stimulated not only the amount of deposited fibrillin-1 and elastin fibers but also their organization perpendicularly to the DEJ. ITP stimulated formation of fibrillin-1 in deeper dermis. In summary, the combination of topical treatment with kinetin and systemic treatment with ITP had complementary beneficial effects in the formation and development of epidermis and dermis.
Keywords: proteiny intermediálních filament; Cells, Cultured; lidé; Adult; Skin Care; Cell Culture Techniques; fibriliny; Elastin; keratinocyty; Female; epidermální buňky; Dermis; lékové interakce; Skin, Artificial; kultivované buňky; Microfilament Proteins; Humans; Drug Interactions; Kinetin; Glycosaminoglycans; elastin; mikrofilamentové proteiny; Filaggrin Proteins; Skin; filagriny; Plant Growth Regulators; regulátory růstu rostlin; péče o kůži; Epidermal Cells; antigen Ki-67; kinetin; fibrilin 1; aplikace lokální; proteiny; škára; kůže; Administration, Topical; ženské pohlaví; buněčné kultury; Fibrillin-1; Proteins; Intermediate Filament Proteins; Keratinocytes; dospělí; Fibrillins; umělá kůže; Ki-67 Antigen; glykosaminoglykany